Effect of in vitro Supplementation of Different Doses of Micronutrients on the Phagocytic Activity of Blood Neutrophils Isolated at Calving from Crossbred Cows - De, Kalyan; Prasad, Shiv; Pal, Shashi; Kaur, Mandheer; Mohanty, A K; Dang, A K (Indian Journal of Dairy Science, 2012)
Peripartum period in cows is considered as the most stressful period and maximum suppression in the phagocytic activity (PA) of neutrophils occurs at calving. To study the effect of micronutrients on the in vitro PA of blood neutrophils, blood samples were taken from freshly calved Karan Fries cows and their neutrophils were isolated. Four micronutrients (Î±-tocopherol, Vitamin A, Copper and Zinc) were supplemented in vitro to the culture of neutrophils and yeast cells/ zymosan at the levels of 0 (control), 5, 10, 25, 50, 75, 100 and 150 percent. PA of blood neutrophils was estimated both by microscopic and nitro blue tetrazolium (NBT) assay. Supplementation of Î±-tocopherol at a concentration of 3.483 Î¼M (75%), Vitamin A (VA) at a concentration of 1.397 Î¼M (50%), copper (Cu) at a concentration of 2.361 Î¼M (25%) and zinc (Zn) at the concentration of 9.176 Î¼M (75%) showed maximum PA. Excess supplementation of Cu at 14.164 Î¼M (150%) significantly (P